Variability in meteorological parameters and their impact on evapotranspiration in a humid zone of Pakistan. (9th December 2019) - Adnan, Shahzada; Ullah, Kalim; Ahmed, Rehan
Abstract: Pakistan lies in the region over the globe where effects of climate change due to global warming are more likely to occur. These climatic changes are reflected in significant gradual fluctuations in measurements of meteorological parameters. Agricultural activity in any region depends upon the role of components of hydrological cycle over the region. An important component of hydrological cycle is evapotranspiration (ET), which is closely linked with changes in meteorological parameters. This study investigates impact of probable variation in four important meteorological parameters i.e. temperature ( T ), net solar radiation ( R n ), vapour pressure ( e a ) and wind speed ( U ) on ET to estimate possible changes in reference ET in a humid zone of Pakistan by employing observed climatological records for 30 years (1981–2010). Analyses are done on the basis of possible ±20% changes in climatological mean values of the observed meteorological parameters. The analyses indicate that 20% rise in observed values of T, R n and U increases value of total (annual) ET demand in the zone up to 11.93%, 16.37% and 2.83% respectively, and 20% rise in the observed values of vapour pressure decreases value of total (annual) ET till −2.5%. Moreover, the analyses also showed that ET is more sensitive to T and R n in monsoon, vapour pressure in winter, and to wind speed in summer. Hence, this study might be useful in planning and formulating future strategies to meet expected future water requirements due to global warming in humid zone of Pakistan and its surrounding region. Abstract : Location of the humid zone of Pakistan and 11 meteorological stations.